Practical process research and development : a guide for organic chemists - Anderson, Neal G.; Anderson, Neal G. (Amsterdam ; Boston : Academic Press, 2012)
Designed to provide a comprehensive, step-by-step approach to organic process research and development in the pharmaceutical, fine chemical, and agricultural chemical industries, this book describes the steps taken, following synthesis and evaluation, to bring key compounds to market in a cost-effective manner. It describes hands-on, step-by-step, approaches to solving process development problems, including route, reagent, and solvent selection; optimising catalytic reactions; chiral syntheses; and "green chemistry." Second Edition highlights: . Reflects the current thinking in chemical process R & D for small molecules . Retains similar structure and orientation to the first edition. . Contains approx. 85% new material . Primarily new examples (work-up and prospective considerations for pilot plant and manufacturing scale-up) . Some new/expanded topics (e.g. green chemistry, genotoxins, enzymatic processes) . Replaces the first edition, although the first edition contains useful older examples that readers may refer to Provides insights into generating rugged, practical, cost-effective processes for the chemical preparation of "small molecules" Breaks down process optimization into route, reagent and solvent selection, development of reaction conditions, workup, crystallizations and more Presents guidelines for implementing and troubleshooting processes.
"Designed to provide a comprehensive, step-by-step approach to organic process research and development in the pharmaceutical, fine chemical, and agricultural chemical industries, this book describes the steps taken, following synthesis and evaluation, to bring key compounds to market in a cost-effective manner. It describes hands-on, step-by-step, approaches to solving process development problems, including route, reagent, and solvent selection; optimising catalytic reactions; chiral syntheses; and green chemistry"--
Introduction Chapter 1. Introduction to the role of process development Chapter 2. Route selection Chapter 3. Reagent selection Chapter 4. Solvent selection Chapter 5. Running the reaction Chapter 6. Water as process consideration Chapter 7. In-process assays and in-process controls Chapter 8. Optimizing the reaction by minimizing impurity formation Chapter 9. Optimizing organometallic processes Chapter 10. Workup, chromatography, and preliminary purification Chapter 11. Purification, crystallization, and isolation Chapter 12. Final product form and impurities Chapter 13. Refining the process for simplicity, ruggedness & impurities Chapter 14. Continuous processing as an alternative to batch processing Chapter 15. Scale-up concerns and process implementation Chapter 16. Trouble-shooting Chapter 17. Trends and perspective Indices: reagent type, reaction type, and regular index including abbreviations.
Revised edition of: Practical process research & development. c2000.
Includes bibliographical references and indexes.
Keywords: Chemical processes; SCIENCE -- Chemistry -- Physical & Theoretical; Chemical processes